معوقات تطبيق إدارة الجودة الشاملة في كلية التربية دراسة ميدانية مقارنة لآراء عينتين من طلاب كليتي التربية بجامعتي البعث وتشرين - حنا, فاضل (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى التعرف على معوقات تطبيق إدارة الجودة الشاملة في كلية تربية جامعتي البعث وتشرين من وجهة نظر الطلبة في الجامعتين، وكذلك التعرف على الفروق في وجهة نظر الطلبة تبعاً لمتغيري الجامعة والمستوى الدراسي. اشتملت عينة البحث على (480) طالباً وطالبة في كلية التربية بجامعة البعث، و(460) في كلية التربية بجامعة تشرين، للعام الدراسي 2009 – 2010. ولتحقيق هدف البحث صممت استبانة احتوت (59) فقرة، وزعت إلى خمسة مجالات تتضمن المعوقات (الإدارية، والبشرية، والمادية، والأكاديمية، والفنية). أظهرت النتائج أن (42.6%) من أفراد العينة في جامعة البعث اتفقوا على تواجد المعوقات المذكورة في الإستبانة بدرجة عالية، مقابل (38.58%) بدرجة متوسطة، في حين أن (19.61%) رأوا أن هذه المعوقات موجودة بدرجة ضعيفة. ورأى (44.51%) من أفراد العينة أن معوقات التطبيق متواجدة بدرجة عالية في جامعة تشرين، مقابل (42.04%) رأوا أنها متواجدة بدرجة متوسطة، و(13.46%) بدرجة ضعيفة. كما وجدت فروق دالة بين الطلبة الجامعيين وطلبة الدراسات العليا، وبين الجامعتين أيضاً. The purpose of the research was to study the attitudes of Al-Baath and Tishreen Universities education Students in Barriers on the implementing of the Total Quality Management, and to study the differences of such attitudes according to variables (University and study level). The sample included (480) students of education Students in Al-Baath University, and (460) of education Students in Tishreen University, for the academic year 2009/2010. To achieve the objective of the research, a questionnaire, including (59) items, was distributed to five areas for Barriers (Administrative, humanity, materialism, academy, technicality). The final results showed that (42.6%) of the examined samples approved of Barriers with high degree in Al-Baath University, where (38.58%) were found to agree with middle degree, and (19.61%) with little degree. In Tishreen University (44.51%) of the examined sample approved of Barriers with high degree, whereas (42.04%) were found to agree with middle degree, and (13.46%) with little degree. In fact, there are differences between the undergraduate and postgraduate students, also between the two Universities.